An Assessment of Receiver Algorithms for Distributed Massive MIMO Systems - Gashtasbi, Ali (2024)
Funding Information: This work is funded by FCT/MCTES through national funds and when applicable co-funded by EU funds under the projects UIDB/EEA/50008/2020 and 2022.03897. PTDC. Funding Information: We acknowledge the support of FCT/MCTES, as described above under \u201CFunding\u201D. We also acknowledge the support of Autonoma TechLab for providing an interesting environment to carry out this research. Publisher Copyright: © 2024 by the authors.